CFD-DEM and Experimental Study of Bubbling in a Fluidized Bed. (December 2015) - Khawaja, Hassan A.
In this study, phenomenon of bubbling is investigated using CFD-DEM and experiments. A CFD-DEM simulation is setup to model the fluidized beds of different sizes. Geldart D particles of 1.2 mm diameter and 1000 Kg/m 3 density are modelled. Study revealed different types of fluidization regimes as stated in the literature. An experimental setup is built to obtain the results for the comparison. Comparison revealed that results obtained from both methodologies; CFD-DEM and experiments are in reasonable agreement.